Pengaruh Kemampuan Mengakses dan Memahami Informasi Peserta KKN DR UIN Jakarta Terhadap Efikasi Diri Pencegahan Penyebaran Covid-19 di Masyarakat - Wisudani, Salshabilla Ayu Fortuna; Azwar, Muhammad (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2024)
Background: One activity that students usually do before the end of the semester is to participate in KKN (Real Work Lecture). In 2020 and 2021 UIN Jakarta conducted a KKN-DR (Real Work Lecture from Home) activity, which was a from adoption of KKN during the Covid-19 pandemic. The pandemic situation has made almost all human activities take place online, which of course requires the ability to access and understand good information.Objective: The purpose of this research is to determine whether there is a significant influence of the ability to access and understand information on self-efficacy in preventing the spread of Covid-19.Methods: This research is associative quantitative research using multiple linear regression analysis.Results: The ability to access and understand information by UIN Jakarta KKN-DR participants did not have a significant effect on self-efficacy in preventing the spread of Covid-19. Simultaneously, the ability to access and understand information only contributed 0.9%, while 99.1% of self-efficacy was influenced by other factors, such as social support, motivation, availability of infrastructure, and economic conditions.Conclusion: Although the level of health information literacy of KKN-DR participants is relatively high, it is not enough to influence self-efficacy in preventing the spread of Covid-19. External factors, such as social support and public awareness are more dominant in the formation of self-efficacy. Implications, the importance of health socialization and education programs that involve various parties, including families and local communities, to increase community self-efficacy in preventing the spread of Covid-19. KKN-DR participants are expected to be able to play an active role in promoting health information literacy effectively to the community